Social Engagement of Elementary-Aged Children With Autism Live Animation Avatar Versus Human Interaction - Kellems, Ryan O.; Charlton, Cade T.; Black, Brooke; Bussey, Heidi; Ferguson, Rachel; Gonçalves, Bruna F.; Jensen, Mikaela; Vallejo, Sara (Journal of special education technology, 2023)
Social engagement is critical to the personal and social development of children. Individuals with Autism Spectrum Disorder (ASD) often exhibit low levels of social engagement with peers and adults, with clearly fewer instances of eye contact, initiation, joint attention, and empathy. Given the pivotal role of social engagement, procedures that naturally evoke higher rates of social engagement may be critical. Prior research suggests that cartoons and other animated characters are more appealing to children with ASD than traditional face-to-face interactions with adults. However, this assertion lacks consistent empirical support. In this study, five elementary age students with ASD participated in a series of interactions with adults and live animation avatars. An alternating treatments design was used to evaluate participants’ social engagement comparing their interactions with avatars to those with humans. Data show all five participants were consistently more attentive to the avatar than to human interventionists. In addition, all participants and their parents indicated the procedures were socially valid (i.e., preferred, feasible, and effective).